PROJECT DATA-SPORT (Developing Analytical Thinking and Academic Skills through Sports Performance Observation, Reflection, and Tracking): Enhancing Literacy, Numeracy, and Life Skills Competencies through Fitness and Sports Data Integration in Senior High (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Physical Education provides opportunities for integrating academic competencies such as analytical thinking, literacy, and numeracy through performance-based activities. However, many Physical Education programs focus primarily on physical participation without maximizing the use of sports performance data as a learning resource. This study examined the effectiveness of PROJECT DATA-SPORT (Developing Analytical Thinking and Academic Skills through Sports Performance Observation, Reflection, and Tracking) in enhancing literacy, numeracy, and life skills competencies among Senior High School students through sports and fitness data integration.This study utilized a quantitative school-based action research design conducted among forty (40) Senior High School students during the School Year 2025–2026. The intervention involved structured observation, recording, analysis, and reflection of sports performance indicators such as time, distance, repetitions, and fitness scores. Data were collected using a researcher-made four-point Likert scale questionnaire, performance tracking sheets, and reflection logs. The collected data were analyzed using weighted mean and descriptive statistics.Results revealed that the implementation of PROJECT DATA-SPORT significantly enhanced students’ analytical thinking, numeracy, and life skills competencies. Students demonstrated a very high level of analytical thinking through sports data analysis (overall mean = 3.37), indicating their ability to interpret and evaluate performance indicators. The project also improved students’ numeracy skills in computing and organizing sports performance data (overall mean = 3.31). In addition, students developed stronger life skills such as self-discipline, goal setting, and self-monitoring (overall mean = 3.40). Engagement in sports data observation and reflection activities was also rated very high (overall mean = 3.38), suggesting that integrating performance tracking increased students’ motivation and participation in Physical Education classes.The findings conclude that integrating sports performance data in Physical Education significantly enhances students’ analytical thinking, numeracy skills, and life skills development. PROJECT DATA-SPORT demonstrates that Physical Education can serve as an interdisciplinary platform for promoting academic competencies while improving physical fitness engagement. Schools are encouraged to institutionalize sports data integration strategies to support holistic learning and strengthen literacy and numeracy development in Senior High School students.